Dynamic common correlated effects of public debt on energy poverty alleviation in OIC member countries: Does institutional performance matter? - Fatima Farooq; Aurangzaib; Muhammad Faheem; Muhammad Ali Gardezi (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2022)
Extensive literature explored debt-growth, growth-energy usage, and growth-poverty link. However, the debt and energy poverty (EP) has received less focus. Despite having a significant impact of these two on economic performance and millions of people's lives. This study employs a modern sets of econometrics approach to resolve the cross-sectional dependency (CSD) and heterogeneity influence of debt on EP alleviation and also explore the moderating role of institutional quality (IQ) from 2000 to 2017 in developing countries of Organization of Islamic Cooperation (OIC). Energy poverty alleviation index is obtained by recruiting four different indicators of energy poverty. We employ dynamic common correlated effect estimator introduced by Chudik and Pesaran (2015) that is suitable in case of cross-sectional dependence and slope heterogeneity. Long run outcomes of the study disclose nonlinear association between public debt and EP alleviation indicating that public debt is conducive for EP reduction up to certain level, but after that, any additional public debt hurts the energy poverty alleviation. Results of the interaction term of the study show that IQ strongly impacts the effect of public debt. On the base of empirical outcomes, it is recommended that public debt should be maintained at a certain level and also the developing countries of OIC should strength their institutional efficiency as it enhances the EP alleviation. This is the novel study that investigates properly the role of institutional performance in debt-energy poverty link in OIC developing countries.
Keywords: 330; public debt; energy poverty; institutional quality; dynamic common correlatedeffects; OIC countries